The U.S. Army in the War of 1812 : an operational and command study - Quimby, Robert S. (Michigan State University Press, 1997)
This two-volume work by historian Robert Quimby presents a comprehensive and detailed analysis of military strategy, operations, and management during one of America's most neglected and least understood military campaigns, the War of 1812. With causes that can be traced to the epic contest against Napoleon in Europe beginning in 1803, the war itself was the first conducted by the young Constitutional government of the United States. Quimby demonstrates that failed American initiatives at the beginning of hostilities shattered the unrealistic optimism of the war's staunchest advocat.